If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + -4) = 5x + -7 Reorder the terms: (2 + x)(x + -4) = 5x + -7 Reorder the terms: (2 + x)(-4 + x) = 5x + -7 Multiply (2 + x) * (-4 + x) (2(-4 + x) + x(-4 + x)) = 5x + -7 ((-4 * 2 + x * 2) + x(-4 + x)) = 5x + -7 ((-8 + 2x) + x(-4 + x)) = 5x + -7 (-8 + 2x + (-4 * x + x * x)) = 5x + -7 (-8 + 2x + (-4x + x2)) = 5x + -7 Combine like terms: 2x + -4x = -2x (-8 + -2x + x2) = 5x + -7 Reorder the terms: -8 + -2x + x2 = -7 + 5x Solving -8 + -2x + x2 = -7 + 5x Solving for variable 'x'. Reorder the terms: -8 + 7 + -2x + -5x + x2 = -7 + 5x + 7 + -5x Combine like terms: -8 + 7 = -1 -1 + -2x + -5x + x2 = -7 + 5x + 7 + -5x Combine like terms: -2x + -5x = -7x -1 + -7x + x2 = -7 + 5x + 7 + -5x Reorder the terms: -1 + -7x + x2 = -7 + 7 + 5x + -5x Combine like terms: -7 + 7 = 0 -1 + -7x + x2 = 0 + 5x + -5x -1 + -7x + x2 = 5x + -5x Combine like terms: 5x + -5x = 0 -1 + -7x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '1' to each side of the equation. -1 + -7x + 1 + x2 = 0 + 1 Reorder the terms: -1 + 1 + -7x + x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -7x + x2 = 0 + 1 -7x + x2 = 0 + 1 Combine like terms: 0 + 1 = 1 -7x + x2 = 1 The x term is -7x. Take half its coefficient (-3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. -7x + 12.25 + x2 = 1 + 12.25 Reorder the terms: 12.25 + -7x + x2 = 1 + 12.25 Combine like terms: 1 + 12.25 = 13.25 12.25 + -7x + x2 = 13.25 Factor a perfect square on the left side: (x + -3.5)(x + -3.5) = 13.25 Calculate the square root of the right side: 3.640054945 Break this problem into two subproblems by setting (x + -3.5) equal to 3.640054945 and -3.640054945.Subproblem 1
x + -3.5 = 3.640054945 Simplifying x + -3.5 = 3.640054945 Reorder the terms: -3.5 + x = 3.640054945 Solving -3.5 + x = 3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + x = 3.640054945 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + x = 3.640054945 + 3.5 x = 3.640054945 + 3.5 Combine like terms: 3.640054945 + 3.5 = 7.140054945 x = 7.140054945 Simplifying x = 7.140054945Subproblem 2
x + -3.5 = -3.640054945 Simplifying x + -3.5 = -3.640054945 Reorder the terms: -3.5 + x = -3.640054945 Solving -3.5 + x = -3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + x = -3.640054945 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + x = -3.640054945 + 3.5 x = -3.640054945 + 3.5 Combine like terms: -3.640054945 + 3.5 = -0.140054945 x = -0.140054945 Simplifying x = -0.140054945Solution
The solution to the problem is based on the solutions from the subproblems. x = {7.140054945, -0.140054945}
| 10-6*2+9/3= | | 7x=-24+x | | 3x-5y-6=0 | | 5x^3+3x^2+2x+8=0 | | 7d-2=4(d-1) | | w^2+14wx+49x^2=0 | | 1/f=0.6(1/4+1/6) | | y=(2x+9)^1/4 | | 5x+60=75 | | (x+yi)+(3-3i)=18 | | 6x^2+12x=-9 | | 3x-(11-2x)=4 | | x/3+3/x=0 | | 2x+x-5=10 | | 2(x-5)+y=10 | | 16x-2(3)=74 | | 16(2+y)-2y=74 | | 3X+6Y=288 | | 288=(3x+6y) | | 1+y+2y=12 | | 288=3X+6Y | | 8x^3-x^4=0 | | 2+2y=12 | | (100+100j)/(20+10j) | | 2ab-5ab+6ab-3ba= | | 3(1+y)-y=7 | | 9+2=910 | | 12ab-6ba-ba-7ab= | | (x+6)+(x-34)=100 | | 2x+3(7)=29 | | 2(4)+3y=29 | | x+13=4x-2 |